Computed corrections for recollision effects on ionization and x-ray production cross sections obtained in positron-impact studies. (February 2023) - Chen, H.; Wu, Y.; Li, Y.D.; Yang, C.X.; Liu, Z.H.
Abstract: The accurate experimental measurement of inner-shell ionization cross sections induced by positrons near the threshold energy is of great significance both for theory and practical application. So far, there are few published experimental data in this field, most of which involve a slow positron beam device and acceleration fields to achieve the desired collision energies. Most previous experimental studies, in which a negative acceleration potential was applied to the target, neglected to consider how backscattered positrons might be accelerated back to the target, generating surplus characteristic x-rays and inflating the cross-section estimates derived therefrom. Using Geant4 and Ansys Maxwell to simulate charged-particle transport, the experimental collision process in the negative high-voltage electromagnetic field of the target chamber is simulated realistically in this paper. Through the simulation process, the effect of the negative high-voltage electromagnetic field on backscattered positrons, hence on ionization and characteristic x-ray production cross sections, is obtained. We then estimate corrections for previously published experimental Ti K-shell ionization cross sections and Ag-Lαβγ, Bi-Mαβ, Pb-Mαβ x-ray production cross sections obtained by positron impact. In addition, we use simulation to demonstrate that such undesired effects can be suppressed by adjusting the size of the target and the tilt angle between the target normal and the positron beam axis. Highlights: The contribution share of the negative high-voltage electromagnetic field is evaluated. The published data are modified by means of the realistic simulation measurement based on Monte Carlo. An optimized scheme of the target chamber is proposed.